Elly Peterson "mother" of the moderates - Fitzgerald, Sara, 1951- (University of Michigan Press, 2011)
"A magisterially written, well-researched, informative, and entertaining biography of a woman who helped throw open the doors to broader participation and power for women in the Republican Party and American politics."--Dave Dempsey, author of William G. Milliken : Michigan's Passionate Moderate. Elly Peterson was one of the highest ranking women in the Republican Party. In 1964 she ran for a Michigan seat in the U.S. Senate and became the first woman to serve as chair of the Michigan Republican Party. During the 1970s she grew disenchanted with the increasing conservatism of her party, united with other feminists to push for the Equal Rights Amendment and reproductive choice, battled Phyllis Schlafly to wrest control from her of the National Federation of Republican Women, and became an independent. Elly Peterson's story is a missing chapter in the political history of Michigan, as well as the United States. This new biography, written by Sara Fitzgerald (a Michigan native and former Washington Post editor), finally gives full credit to one of the first female political leaders in this country. When Peterson retired in 1970 as assistant chairman of the Republican National Committee, David Broder of the Post wrote that her abilities would have earned her the national chairmanship were it not for the unwritten sex barrier that both parties have erected around that job."--